Mental skills in Serbian handball players: In relation to the position and gender of players - Jakšić, Damjan; Trbojević Jocić, Jovana; Maričić, Stefan; Miçooğullari, Bülent O.; Sekulić, Damir; Foretić, Nikola; Bianco, Antonino; Drid, Patrik (Frontiers in Psychology, 2022)
Objectives: Despite the potential link between mental skills and athletic performance, little is done to examine handball players' present level of mental skills concerning their performance. To begin with, the study has three folded aims; the first one is to examine the factor structure of Bull's Mental Skills Questionnaire, which was developed in the UK to measure selected mental skills of the Serbian population. The second aim is to determine gender differences in those mental skills, and the third aim is to determine differences between the playing positions in the mental skills of handball players to create a mental profile of Serbian handball players. Method: The sample consisted of 170 handball players, aged 14 to 39, who have played handball on a professional and semi-professional. The modified exploratory factor analysis was used to determine the latent dimensions of the Bull's Mental Skills Questionnaire. For examining gender differences in the manifestation of mental skills Mann-Whitney U test was used. Results: Compared to the original structure of the questionnaire, which singles out seven factors of mental skills (imagery ability, mental preparation, self-confidence, anxiety and worry management, concentration ability, relaxation ability, and motivation), five factors were singled out in the sample of Serbian male and female handball players (anxiety and concentration management – α=0.74; self-confidence – α=0.75; relaxation ability– α=0.66; mental preparation– α=0.68, and imagery ability– α=0.66). With these five subscales as dependent variables, results of the Mann-Whitney U test show that there are significant gender differences in variable anxiety and concentration management (U=2893.5, p=0.049) and relaxation ability (U=2833.0, p=0.031). Female handball players score higher on anxiety and concentration management and lower on relaxation ability. When playing positions are in question, results of Kruskal-Wallis`s one-way analysis of variance, i.e., Mann-Whitney's post hoc analysis, suggest that statistically significant differences were observed between wingers and center backs and wingers and goalkeepers in the imagery ability. Conclusions: The Bull’s Mental Skills Questionnaire in Serbian sample of handball players show satisfactory psychometric characteristics but has singled out five factors of mental skills compared to the original questionnaire.